Efecto de la densidad sobre el crecimiento en fase de engorde del mejillón, Mytilus edulis platensis, en el golfo San Jorge, Patagonia argentina - Isola,Tomás E. (Universidad de Valparaíso. Facultad de Ciencias del Mar, 2020)
Abstract: The aim of this study was to determine the stock density effect on size and biomass on mussel Mytilus edulis platensis, at growth up phase ropes. These ropes were made using three initial stocking densities: 200, 300 and 400 mussels m-1 and hung on in a longline at Belvedere site on San Jorge gulf, Argentina. Stock density showed no influence on individual mussel biomass. Higher growth length was obtained at higher densities. According to these results, when the mussels are in the fattening or thinning out phase, the optimum stocking density would be 300 to 400 mussels m-1.